The concptual discourse of hypostasis in contemporary ceramic prodution - حنين وسام محمد; رنا ضاحي عبد الكريم (Basrah Arts Journal, 2026)
This research examines the conceptual discourse of the concept of habitus in contemporary global ceramics. The researcher sought to shed light on this concept and interpret it as an element that reflects the social and cultural formations that permeate the creative process. The research is composed of four integrated chapters. The first chapter includes the general framework of the research, which addresses the study problem by posing questions about how the conceptual discourse of habitus is formed and its impact on shaping meaning within ceramic work. This chapter also presents the importance of the research, its objectives for the period extending from 2015 to 2023, and its temporal, spatial, and methodological boundaries, defining the basic terms underlying the study. The second chapter focuses on the theoretical framework by reviewing the conceptual discourses of habitus and linking these insights to the ceramic’s context. This chapter, in the first section, discusses the discourse of habitus in contemporary ceramics. The second chapter addresses the conceptual context of habitus in contemporary ceramics, the transformations that have occurred in ceramic discourse under postmodern concepts, and their implications for shaping the conceptual content of contemporary artworks. The third chapter addresses the methodological procedures adopted by the researcher. The research community and its sample were identified, consisting of four global ceramic models selected according to representative criteria consistent with the study’s objectives. The third chapter, "Research Procedures," encompasses the research community and sample, the research methodology, research tools, and the steps of the adopted analysis. The fourth chapter presents the researcher’s findings: 1-The demolition of the discourse of habitus for grand narratives represents a decisive turning point in the path of aesthetic and cognitive thinking within the structure of contemporary ceramic work. The potter is no longer subject to central patterns or strict references that have long been used. 2- The idea of ​​an open discourse presented by the addressee to complete the construction of meaning has transformed ceramic formations into vibrating discourses whose mission is to undermine and dismantle the rigid conceptual landscape.